Decomposing the Bid–ask Spread in Multi‐Dealer Markets. (15th October 2015) - Bleaney, Michael; Li, Zhiyong
Abstract: In this paper, we modify the Huang and Stoll spread‐decomposing model to fit multi‐dealer markets. In a multi‐dealer market, individual dealers can rebalance their inventories either by trading with other dealers or by changing the quote price. Our modified model captures this feature. Using transaction data from the Reuters D2000‐1 system, we find that the order‐processing and inventory control components of the spread in the foreign exchange market are relatively small and dealers may tolerate the unwanted inventory to keep the spread small to attract informed orders. The asymmetric information component carries the biggest weight. We study the time pattern of the spread and its components. The spread varies significantly with the time of day, but the inventory control and asymmetric information components do not. Copyright © 2015 John Wiley & Sons, Ltd.